2021
DOI: 10.1111/jth.15208
|View full text |Cite
|
Sign up to set email alerts
|

Should emicizumab be used in patients with acquired hemophilia A?

Abstract: Emicizumab is currently approved to prevent bleeding in patients with congenital hemophilia A with or without neutralizing antibodies (inhibitors) against factor VIII (FVIII). Here, we present a case‐based discussion of its potential use in acquired hemophilia A (AHA), a severe bleeding disorder caused by autoantibodies against FVIII. State‐of‐the‐art management is based on bypassing agents (recombinant factor VIIa, activated prothrombin complex concentrate) and recombinant porcine FVIII; immunosuppressive the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 41 publications
(97 reference statements)
1
28
0
Order By: Relevance
“…This explains the need for aggressive immunosuppressive therapy. 17 , 18 Based on the available data and our own experience, emicizumab’s major advantages include its ease of use, rapid haemostatic prophylactic efficacy and reduced requirement of aggressive immunosuppressant agents. This last advantage should not be overlooked, as infectious complications related to immunosuppression are the primary death cause in AHA patients.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains the need for aggressive immunosuppressive therapy. 17 , 18 Based on the available data and our own experience, emicizumab’s major advantages include its ease of use, rapid haemostatic prophylactic efficacy and reduced requirement of aggressive immunosuppressant agents. This last advantage should not be overlooked, as infectious complications related to immunosuppression are the primary death cause in AHA patients.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“… 1 , 3 , 13 , 14 Finally, in our experience and as reported in the literature, transfusion requirements have decreased rapidly from the first emicizumab dose onwards, thereby reducing the risk of ischaemic anaemia-related complications, as well as that of repeated transfusions, including alloimmunization, volume overload, pulmonary oedema and iron overload. 18 …”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The emicizumab use reported in this population to date 3,4 has been immediately following diagnosis and used in conjunction with bypassing agents (BPA) for the treatment of the presenting haemorrhagic event. 4,5 Reported benefits in upfront emicizumab use included earlier discharge and the ability to use less immunosuppression with less adverse effects. Emicizumab reportedly resulted in haemostasis and discontinuation of BPAs after 1.5 (1-4) days with the concurrent use of immunosuppression (steroids and/or rituximab), and no recurrent bleeding was observed.…”
Section: E T T E R T O T H E E D I T O R Emicizumab Reduces Re-hospitalization For Bleeding In Acquired Haemophilia Amentioning
confidence: 99%
“…Four such patients were hospitalized for acute bleeding in 2020. All were treated with recombinant porcine VIII (rpFVIII) as previously reported, 5 or with recombinant activated factor VII (rFVIIa) if they had developed antiporcine FVIII (anti-pFVIII) antibodies. Emicizumab (3 mg/kg subcutaneous weekly for 4 doses, followed by 1.5 mg/kg weekly) was initiated after resolution of bleeding and prior to discharge.…”
Section: E T T E R T O T H E E D I T O R Emicizumab Reduces Re-hospitalization For Bleeding In Acquired Haemophilia Amentioning
confidence: 99%
“…Bypassing agents could be stopped after 1.5 days. Several other cases using other dose regimens of emicizumab in AHA have been reported and are reviewed by Tiede et al 27 It was concluded that emicizumab may be able to shorten the duration of initial bleeds and recurrent bleeding, but more data from prospective clinical trials is needed.…”
Section: Management Of Bleeding With Hemostatic Agentsmentioning
confidence: 99%